Potential for international spread of wild poliovirus via travelers - Wilder-Smith, Annelies; Leong, Wei-Yee; Lopez, Luis Fernandez; Amaku, Marcos; Quam, Mikkel; Khan, Kamran; Massad, Eduardo (BMC medicine, 2015)
The endgame of polio eradication is hampered by the international spread of poliovirus via travelers. In response to ongoing importations of poliovirus into polio-free countries, on 5 May 2014, WHO’s Director-General declared the international spread of wild poliovirus a public health emergency of international concern. Our objective was to develop a mathematical model to estimate the international spread of polio infections.
Gesehen am 02.07.2020